Channel electrode voltammetric and in situ electrochemical ESR studies of comproportionation of methyl viologen in acetonitrile - Lee, C; Eklund, J; Dryfe, R; Compton, R (1996)
Two redox processes of methyl viologen (+2/+, +/0) in acetonitrile were investigated by using channel electrode voltammetric and in situ electrochemical ESR methods. Two separated unequal plateau currents of the first (+2/+) and second (+/0) redox processes of the viologen were observed in the channel electrode voltammograms and showed a cube-root depedndence on the electrolyte flow rate, respectively. The simple Levich analysis resulted in two different diffusion coefficients of D+2=2.2×10-5 cm2/s and D+=3.0×10-5 cm2/Vs from the limiting currents. In situ electrochemical ESR studies were performed for the monocation radicals generated at the potentials of the two plateau currents in the electrolyte flow range 1.3×10-1≥ vf ≥:2.7×10-3 cm3/s. Backward implicit finite difference method was employed to simulate the electrochemical kinetic problem of two sequential electron transfers (MV+2+e → ← MV+, MV++e ⇄MV0) coupled with reversible comproportionation (MV2+ + MV0kf→ ← kb2MV+). kf was found to be greater than 106 M-1 s-1.